Coarctation of the aorta and post-stenotic aneurysm formation. Issue 5 (November 1990) - Mitchell, I M; Pollock, J C
Abstract : Despite earlier angiography, post-stenotic aneurysm of the aorta was an unexpected finding at operation in two patients with coarctation. One aneurysm was found in an intercostal artery in a 19 year old man and the other was a false aneurysm just distal to the coarctation site in a 7 year old boy. These aneurysms are fragile, apt to rupture, and difficult to diagnose preoperatively. Though local factors such as jet streams and bacterial endocarditis may influence their formation there must be an underlying generalised weakness in the arterial wall. A coarctation should not be regarded as an isolated arterial abnormality because it may be a feature of a more generalised disease. Because of the risk of rupture, which may not be prevented by antihypertensive treatment, operation should not be delayed in any age group.